High-dose radiotherapy with short-term or long-term androgen deprivation in localised prostate cancer (DART01/05 GICOR): a randomised, controlled, phase 3 trial - Zapatero, Almudena; Guerrero, Araceli; Maldonado, Xavier; Alvarez, Ana; Segundo, Carmen Gonzalez San; Rodríguez, Maria Angeles Cabeza; Macias, Victor; Olive, Agustí Pedro; Casas, Francesc; Boladeras, Ana; de Vidales, Carmen Martín; de la Torre, Maria Luisa Vazquez; et al. (The lancet oncology, 2015)
The optimum duration of androgen deprivation combined with high-dose radiotherapy in prostate cancer remains undefined. We aimed to determine whether long-term androgen deprivation was superior to short-term androgen deprivation when combined with high-dose radiotherapy. In this open-label, multicentre, phase 3 randomised controlled trial, patients were recruited from ten university hospitals throughout Spain. Eligible patients had clinical stage T1c–T3b N0M0 prostate adenocarcinoma with intermediate-risk and high-risk factors according to 2005 National Comprehensive Cancer Network criteria. Patients were randomly assigned (1:1) using a computer-generated randomisation schedule to receive either 4 months of androgen deprivation combined with three-dimensional conformal radiotherapy at a minimum dose of 76 Gy (range 76–82 Gy; short-term androgen deprivation group) or the same treatment followed by 24 months of adjuvant androgen deprivation (long-term androgen deprivation group), stratified by prostate cancer risk group (intermediate risk vs high risk) and participating centre. Patients assigned to the short-term androgen deprivation group received 4 months of neoadjuvant and concomitant androgen deprivation with subcutaneous goserelin (2 months before and 2 months combined with high-dose radiotherapy). Anti-androgen therapy (flutamide 750 mg per day or bicalutamide 50 mg per day) was added during the first 2 months of treatment. Patients assigned to long-term suppression continued with the same luteinising hormone-releasing hormone analogue every 3 months for another 24 months. The primary endpoint was biochemical disease-free survival. Analysis was by intention to treat. This study is registered with ClinicalTrials.gov, number NCT02175212. Between Nov 7, 2005, and Dec 20, 2010, 178 patients were randomly assigned to receive short-term androgen deprivation and 177 to receive long-term androgen deprivation. After a median follow-up of 63 months (IQR 50–82), 5-year biochemical disease-free survival was significantly better among patients receiving long-term androgen deprivation than among those receiving short-term treatment (90% [95% CI 87–92] vs 81% [78–85]; hazard ratio [HR] 1·88 [95% CI 1·12–3·15]; p=0·01). 5-year overall survival (95% [95% CI 93–97] vs 86% [83–89]; HR 2·48 [95% CI 1·31–4·68]; p=0·009) and 5-year metastasis-free survival (94% [95% CI 92–96] vs 83% [80–86]; HR 2·31 [95% CI 1·23–3·85]; p=0·01) were also significantly better in the long-term androgen deprivation group than in the short-term androgen deprivation group. The effect of long-term androgen deprivation on biochemical disease-free survival, metastasis-free survival, and overall survival was more evident in patients with high-risk disease than in those with low-risk disease. Grade 3 late rectal toxicity was noted in three (2%) of 177 patients in the long-term androgen deprivation group and two (1%) of 178 in the short-term androgen deprivation group; grade 3–4 late urinary toxicity was noted in five (3%) patients in each group. No deaths related to treatment were reported. Compared with short-term androgen deprivation, 2 years of adjuvant androgen deprivation combined with high-dose radiotherapy improved biochemical control and overall survival in patients with prostate cancer, particularly those with high-risk disease, with no increase in late radiation toxicity. Longer follow-up is needed to determine whether men with intermediate-risk disease benefit from more than 4 months of androgen deprivation. Spanish National Health Investigation Fund, AstraZeneca.